Quelle stratégie de développement durable dans les hôtels en Tunisie ? - Chiraz Ghozzi-Nékhili (VertigO)
Tourism is a big consumer of water. Since, water resources in Tunisia are characterized by scarcity and a pronounced irregularity is management should be done with appropriate strategies. The aim of this paper is to study the behavior of hotels operators in Tunisia in order to identify strategies for water management that would be part of their sustainable development (SD) strategies. Our study was conducted on hotels managed by the Accor group, a leader in the tourism and especially involved Tunisian tourism development and in SD. In regard of the results of this exploratory study, we concluded that the Accor hotels have a SD strategy identified as “engage”. This strategy is based on several activities linked to the water management. But other hotels are more concerned for the cost of water and develop some specific actions that could be considered as “incoming” strategy.